2011
DOI: 10.1161/strokeaha.111.620658
|View full text |Cite
|
Sign up to set email alerts
|

Low Carotid Calcium Score Is Associated With Higher Levels of Glycosaminoglycans, Tumor Necrosis Factor-Alpha, and Parathyroid Hormone in Human Carotid Plaques

Abstract: Background and Purpose-Computed tomography (CT) is used to study coronary artery plaques, but little is known about its potential to characterize plaque composition. This study assesses the relation between carotid calcium score (CCS) by CT and plaque composition, namely extracellular matrix, inflammatory mediators, and calcium metabolites. Methods-Thirty patients with significant carotid stenosis underwent preoperative CT. CCS was quantified by Agaston calcium score. Plaque components were studied histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The connection of high serum concentrations of IL-6 and TNF-α with the presence of unstable plaques assessed in ultrasound examinations has been confirmed by other authors as well [15, 25, 27]. In the present study, no significant differences in TNF-α serum levels depending on the presence of stenosis, its level or clinical manifestation were found, which is in agreement with the results obtained by other authors [23, 28].…”
Section: Discussionsupporting
confidence: 93%
“…The connection of high serum concentrations of IL-6 and TNF-α with the presence of unstable plaques assessed in ultrasound examinations has been confirmed by other authors as well [15, 25, 27]. In the present study, no significant differences in TNF-α serum levels depending on the presence of stenosis, its level or clinical manifestation were found, which is in agreement with the results obtained by other authors [23, 28].…”
Section: Discussionsupporting
confidence: 93%
“…In a recent systematic review of 24 studies, it has been reported that clinically symptomatic carotid plaques have less calcium content than asymptomatic ones [1]. Of interest was this recent report that carotid plaques not so rich in calcium had higher expression of proinflammatory cytokines [2]. These findings support earlier observations that calcium may have a plaque stabilizing role [3], [4].…”
supporting
confidence: 72%
“…Sections were then fixed with Histochoice (Amresco, Solon, OH, USA) and stained for smooth muscle cells (smooth muscle α-actin), macrophages (CD68), neutral lipids (Oil Red O) and intraplaque haemorrhage (Glycophorin A) as previously described [9,10]. Calcified areas in plaques were quantified as described previously [11]. Collagen fibers (yellow) were assessed using Russell-Movat Pentachrome staining.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%